IOT Based Vehicle Crash Investigation System Using Black Box - M. Gowtham,; S. Sreejith,; A. Abarnaa,; S. Dhanush,; N. Harish, (Journal of Electronic Design Engineering, 2020)
India positions first in the quantity of road accident passing over the 195 nations detailed on the world road Insights, 2018 followed by China and US. According to the WHO Worldwide Report on Street Wellbeing 2018, India represents practically 11% of the mishap related passing’ on the world. A sum of 4,67,044 street mishaps have been accounted for by States and Association Regions in the schedule year 2018, guaranteeing 1,51,417 lives and making wounds 4,69,418 people, the report said. Over-speeding represented 64.4% of the people murdered. In excess of 43 lakh cases are pending in the 25 high courts in the nation and more than 8 lakh of these are over 10 years old. Out of the 43 lakhs nearly 20% are accident cases. To overcome this problem we proposed a system to collect the vehicle data for accident investigation and anti-theft system by using Black Box. Vehicle data are collected in real time basis and the data is transmitted to cloud storage and that can be easily access by admin by using unique credentials through mobile application.